2019
DOI: 10.1590/0037-8682-0342-2018
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatic alveolar echinococcosis infringing the inferior vena cava

Abstract: FIGURE A: Abdominal computed tomography/magnetic resonance imaging examination. 1234 The black arrows indicate the lesion of hepatic alveolar echinococcosis; the red arrows, the compressed retrohepatic inferior vena cava; 56 the red arrows, the obstructed inferior vena cava; and the black and white arrows, the compensatory azygos and hemi-azygos veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Radical hepatectomy is the first choice for the treatment of HAE and liver cancer 5,6 . For patients with liver cancer, if they exist extrahepatic metastasis, then they have lost the opportunity of radical surgery 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Radical hepatectomy is the first choice for the treatment of HAE and liver cancer 5,6 . For patients with liver cancer, if they exist extrahepatic metastasis, then they have lost the opportunity of radical surgery 7 .…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β secreted by Kupffer cells is an important factor causing liver damage[ 64 ]. In a previous study[ 36 ], we observed typical chronic granulomatous changes around the lesion, accompanied by lymphocyte infiltration, hepatocyte degeneration and necrosis, and Kupffer cell proliferation and differentiation in tissues from patients with HAE. In this study, we used CD68 to identify Kupffer cells, and confirmed that they play an important role in the marginal zone.…”
Section: Discussionmentioning
confidence: 79%
“…The occurrence and development of parasitic diseases is often accompanied by inflammation[ 34 , 35 ]. In a previous study, we determined that HAE has a clear marginal zone[ 36 ]. However, the role and clinical significance of the NLRP3 inflammasome in HAE remain unclear.…”
Section: Introductionmentioning
confidence: 99%